MICROALGAE METALLOTHIONEIN OPTIMIZATION THROUGH GENETIC ENGINEERING FOR BIOREMEDIATION AND BIOLOGY EDUCATION - Nurul Magfirah; Hartati Hartati (Universitas Medan Area, 2026)
Heavy metal pollution (e.g., Cd, Pb, Hg) threatens aquatic ecosystems due to its persistence, toxicity, and bioaccumulation. Microalgae are promising agents for bioremediation via bioadsorption and intracellular bioaccumulation, but their intrinsic metal uptake is often inadequate under high contamination. This review aimed to synthesize current evidence on metallothionein (MT)-based enhancement of microalgae bioremediation and to map its relevance for project-based and STEM-oriented biology learning. A narrative (descriptive–analytical) literature review was conducted using recent publications (primarily within the last 10 years) on MT/PC mechanisms, microalgae genetic engineering and synthetic biology, genome editing, and biosafety. Content analysis was used to extract and integrate findings. The review indicates that MT functions as a metal buffer, detoxifier, and antioxidant, and that MT performance can be improved through (i) target-gene selection informed by omics and motif/phylogenetic analyses, (ii) construct design with strong/metal-inducible promoters and subcellular targeting, (iii) pathway-level co-engineering (transporters, glutathione/antioxidant systems), and (iv) genome editing (e.g., CRISPR-based knockout of inhibitory regulators). Biosafety-by-design strategies (biocontainment, auxotrophy, closed photobioreactor deployment) are critical for real-world use. Overall, MT-centered engineering offers a feasible route to strengthen microalgae bioremediation and provides an authentic context for integrating biotechnology with socio-scientific issues in biology education.